What are the influence of fishery activities and their implication on marine water pollution? an empirical analysis - Alsaleh, Mohd; Abdul-Rahim, A.S. (Springer, 2024)
A mixture of oil consumption, toxic waste, chemicals, and plastic debris from fisheries operations may dissolve and suck oxygen from marine water, turning saltwater into poison for marine animals and ecosystems, as shown by the invisible marine water catastrophe. The study is to examine the dynamic relationship between the fishing industry and marine water pollution in 27 European countries between 1990 and 2022, with a particular emphasis on the roles played by economic development, governance, fisheries productivity, and the use of fossil fuels. The results show that increasing fishing productivity dramatically increases marine water pollution across most quantiles. Fixed-effect variables were used in conjunction with the Mixed Methods Quantile Regression. Marine pollution is significantly worsened by fishing activity at both the lower and upper quantiles; the effect is stronger at the higher quantiles and less pronounced at the lower ones. Additionally, the statistics show that developed EU14 countries have higher levels of fisheries output than developing EU13 countries, which contributes to a greater degree of contamination of marine waters. Furthermore, compared to the developed EU14 countries, the developing EU13 countries have seen a sharp increase in marine pollution due to the use of fossil fuels. In the developed EU-14 countries, economic expansion reduces the quality of sea water in all quantiles, hence bolstering the growth hypothesis for fish-producing countries. Only the early and later quantiles in the EU14 developed countries showed a statistically significant effect from ocean governance, with a negative influence extending from the first to the sixth quantile. To lessen marine pollution in both EU14 and EU13 countries, policymakers should promote the use of eco-friendly fishing gear, sustainable fishing techniques, and energy technologies like tidal and wave power.